Pengujian Rumah Pengering Daun Kelor Dengan Efek Rumah Kaca (Solar Dryer) Melalui Mekanisme Konveksi Alamiah - Aloysius V.P. Piamat; Verdy A. Koehuan; Muhamad Jafri (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
This research was conducted by experimental study of moringa leaf drying process using ultra violet plastic dryer house (UV solar dryer) through natural convection drying mechanism. The results showed that the final water content of moringa leaves after drying for two days (8 hours) was 54.88 %bb with a total drying rate of 0.417 kg/hour from the assumed initial water content of 80 %bb. While the average drying efficiency of 3.49 % with specific energy consumption (KES) is quite high, which is 127180.77 kJ/kg. The highest specific energy consumption (KES) occurred on the 2nd day test at 200056.37 kJ/kg with the lowest efficiency of 2.154 %, while the lowest KES on the 1st day test was 54305,17 kJ/kg with the highest efficiency of 4.83 %. This phenomenon is very clear the influence of changing environmental weather on the drying process in the drying house. Environmental weather is very influential on the process of drying moringa leaves with a natural convection mechanism using ERK type dryer. Cloudy weather with high humidity will increase the humidity in the dryer house through the water vapor content in the air that enters through the air ducts